Recent advances in understanding/managing eosinophilic esophagitis in adults - Katzka, David A. (F1000Res, 2015)
It is an exciting time for research in eosinophilic esophagitis (EoE). As a new and increasingly prevalent disease, it is receiving considerable attention in the medical world, resulting in a flood of new insights. Clearly, a genetic predisposition seems likely with the identification of abnormalities in thymic stromal lymphopoietin (TSLP), calpain14, and eotaxin-3 genes. There are also well-defined abnormalities described in esophageal epithelial barrier function in these patients. The relationship between gastroesophageal reflux disease (GERD) and EoE remains unclear, but emerging data suggest that the concept of proton pump inhibitor responsive esophageal eosinophilia (PPIREE) may retain less importance, as this subset of patients becomes a likely subset of EoE in general. Finally, we approach the looming issue of long-term maintenance therapy. Although we lack adequate specific data on how to provide long-term pharmacologic treatment, studies clearly show that for most patients, this is a progressive disease that warrants such consideration.